∫exsec⁡x(1+tan⁡x)dx is equal to 

exsecx(1+tanx)dx is equal to 

  1. A

    excosx+C

  2. B

    exsecx+C

  3. C

    exsinx+C

  4. D

    extanx+C

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    Let I=exsecx(1+tanx)dx

    I=exsecxdx+exsecxtanxdx -----i

    Now exsecxdx=secxexdxddxsecxexdxdx

    =exsecxsecxtanxexdx ----ii

     On putting the value from Eq. (ii)inEq. (i),we get 

    I=exsecxexsecxtanxdx+secxtanxexdx+CI=exsecx+C

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.